Spherization of red blood cells and platelet margination in COPD patients. Issue 1 (2nd October 2020) - Zouaoui Boudjeltia, Karim; Kotsalos, Christos; de Sousa, Daniel Ribeiro; Rousseau, Alexandre; Lelubre, Christophe; Sartenaer, Olivier; Piagnerelli, Michael; Dohet‐Eraly, Jérôme; Dubois, Frank; Tasiaux, Nicole; Chopard, Bastien; Van Meerhaeghe, Alain
Abstract: Red blood cells (RBCs) in pathological situations undergo biochemical and conformational changes, leading to alterations in rheology involved in cardiovascular events. The shape of RBCs in volunteers and stable and exacerbated chronic obstructive pulmonary disease (COPD) patients was analyzed. The effects of RBC spherization on platelet transport (displacement in the flow field caused by their interaction with RBCs) were studied in vitro and by numerical simulations. RBC spherization was observed in COPD patients compared with volunteers. In in vitro experiments at a shear rate of 100 s −1, treatment of RBCs with neuraminidase induced greater sphericity, which mainly affected platelet aggregates without changing aggregate size. At 400 s −1, neuraminidase treatment changes both the size of the aggregates and the number of platelet aggregates. Numerical simulations indicated that RBC spherization induces an increase of the platelet mean square displacement, which is traditionally linked to the platelet diffusion coefficient. RBCs of COPD patients are more spherical than healthy volunteers. Experimentally, RBC spherization induces increased platelet transport to the wall. Additional studies are needed to understand the link between the effect of RBCs on platelet transport and the increased cardiovascular events observed in COPD patients. Abstract : Red blood cells (RBCs) in pathological situations undergo biochemical and conformational changes, leading to alterations in rheology involved in cardiovascular events. In the present work, we first analyze the shape of RBCs in stable and exacerbated COPD patients, compared with healthy volunteers. Second, we analyze the effect of the spherization of red blood cells on platelet margination experimentally, both in vitro and in silico .